(untitled) (Simbiótica. Revista Eletrônica, 2025)
This article aimed to investigate and reflect on the experiences of street vendors on the beaches of the suburbs of Salvador, in relation to motherhood and informal work, from the perspective of these workers. Anchored in Social Work Psychology, it adopts a social constructionist reading in dialogue with Actress-Network Theory. Among the main findings, we understand that the meaning of work goes beyond the financial aspect, involving self-recognition, belonging, and personal fulfillment. Work flexibility provides autonomy, but paradoxically contributes to precariousness. The absence of government support is identified as an actant that keeps workers in situations of vulnerability, ensuring only survival. In this way, the need to implement actions that recognize the productive nature of street vendors and their intricate relationship with motherhood was highlighted. This will allow the implementation of support and health measures, aiming to improve working conditions.